Correction to: Experimental determination of the temperature dependence of oxygen-isotope fractionation between water and chitinous head capsules of chironomid larvae - Alex Lombino; Tim Atkinson; Stephen J. Brooks; Darren R. Gröcke; Jonathan Holmes; Vivienne J. Jones; Jim D. Marshall (Journal of Paleolimnology, 2021)

Experimental determination of the temperature dependence of oxygen-isotope fractionation between water and chitinous head capsules of chironomid larvae - Alex Lombino; Tim Atkinson; Stephen J. Brooks; Darren R. Gröcke; Jonathan Holmes; Vivienne J. Jones; Jim D. Marshall (Journal of Paleolimnology, 2021)
Oxygen-isotope values of invertebrate cuticle preserved in lake sediments have been used in palaeoenvironmental reconstructions, generally with the assumption that fractionation of oxygen isotopes between cuticle and water ( $$\upalpha_{\text{cuticle}-\text{H}_{2}\text{O}}$$ α cuticle - H 2 O ) is independent of temperature. We cultured chironomid larvae in the laboratory with labelled oxygen-isotope water and across a range of closely controlled temperatures from 5 to 25 °C in order to test the hypothesis that fractionation of oxygen isotopes between chironomid head capsules and water ( $$\upalpha_{\text{chironomid}-\text{H}_{2}\text{O}}$$ α chironomid - H 2 O ) is independent of temperature. Results indicate that the hypothesis can be rejected, and that $$\upalpha_{\text{chironomid}-\text{H}_{2}\text{O}}$$ α chironomid - H 2 O decreases with increasing temperature. The scatter in the data suggests that further experiments are needed to verify the relationship. However, these results indicate that temperature-dependence of $$\upalpha_{\text{chironomid}-\text{H}_{2}\text{O}}$$ α chironomid - H 2 O should be considered when chironomid δ 18 O is used as a paleoenvironmental proxy, especially in cases where data from chironomids are combined with oxygen-isotope values from other materials for which fractionation is temperature dependent, such as calcite, in order to derive reconstructions of past water temperature.

Increasing nutrient stress reduces the efficiency of energy transfer through planktonic size spectra - Angus Atkinson; Martin K.S. Lilley; Andrew G. Hirst; Andrea J. McEvoy; Glen A. Tarran; Claire Widdicombe; Elaine S. Fileman; E. Malcolm S. Woodward; Katrin Schmidt; Tim J. Smyth; Paul J. Somerfield (Limnology and Oceanography, 2021)
Size‐spectral approaches quantify the efficiency of energy transfer through food webs, but theory and field studies disagree over how changes in temperature, nutrients, and extreme weather impact on this efficiency. We address this at two scales: via 6 years of weekly sampling of the plankton size spectrum at the Plymouth L4 shelf sea site, and via a new, global‐scale, meta‐analysis of aquatic size spectra. The time series showed that with summertime nutrient starvation, the energy transfer efficiency from picoplankton to macroplankton decreased (i.e., steepening slopes of the size spectra). This reflected increasing dominance by small cells and their microbial consumers. The extreme storms in winter 2013/2014 caused high metazoan mortality, steep size‐spectral slopes, and reduced plankton biomass. However, recovery was within months, demonstrating an inbuilt resilience of the system. Both L4 and our meta‐analysis showed steep slopes of normalized size spectra (median −1.11). This reflects much lower values, either of trophic transfer efficiency (3.5%) or predator–prey mass ratio (569), compared to commonly quoted values. Results from the meta‐analysis further showed that to represent energy transfer faithfully, size spectra are best constructed in units of carbon mass and not biovolume, and span a mass range of > 10 7 . When this range is covered, both the meta‐analysis and time series show a dome‐shaped relationship between spectral slopes and plankton biomass, with steepening slopes under increasingly oligotrophic and eutrophic conditions. This suggests that ocean warming could decrease the efficiency of energy transfer through pelagic food webs via indirect effects of increasing stratification and nutrient starvation.

Increasing picocyanobacteria success in shelf waters contributes to long‐term food web degradation - Katrin Schmidt; Antony J. Birchill; Angus Atkinson; Robert J. W. Brewin; James R. Clark; Anna E. Hickman; David G. Johns; Maeve C. Lohan; Angela Milne; Silvia Pardo; Luca Polimene; Tim J. Smyth; et al. (Global Change Biology, 2020)
Continental margins are disproportionally important for global primary production, fisheries and CO 2 uptake. However, across the Northeast Atlantic shelves, there has been an ongoing summertime decline of key biota—large diatoms, dinoflagellates and copepods—that traditionally fuel higher tropic levels such as fish, sea birds and marine mammals. Here, we combine multiple time series with in situ process studies to link these declines to summer nutrient stress and increasing proportions of picophytoplankton that can comprise up to 90% of the combined pico‐ and nanophytoplankton biomass in coastal areas. Among the pico‐fraction, it is the cyanobacterium Synechococcus that flourishes when iron and nitrogen resupply to surface waters are diminished. Our field data show how traits beyond small size give Synechococcus a competitive edge over pico‐ and nanoeukaryotes. Key is their ability to grow at low irradiances near the nutricline, which is aided by their superior light‐harvesting system and high affinity to iron. However, minute size and lack of essential biomolecules (e.g. omega‐3 polyunsaturated fatty acids and sterols) render Synechococcus poor primary producers to sustain shelf sea food webs efficiently. The combination of earlier spring blooms and lower summer food quantity and quality creates an increasing period of suboptimal feeding conditions for zooplankton at a time of year when their metabolic demand is highest. We suggest that this nutrition‐related mismatch has contributed to the widespread, ~50% decline in summer copepod abundance we observe over the last 60 years. With Synechococcus clades being prominent from the tropics to the Arctic and their abundances increasing worldwide, our study informs projections of future food web dynamics in coastal and shelf areas where droughts and stratification lead to increasing nutrient starvation of surface waters.

Comment. What drives plankton seasonality in a stratifying shelf sea? Some competing and complementary theories - Angus Atkinson; Luca Polimene; Elaine S. Fileman; Claire E. Widdicombe; Andrea J. McEvoy; Tim J. Smyth; Nicolas Djeghri; Sévrine F. Sailley; Louise E. Cornwell (Limnology and Oceanography, 2018)
The Plymouth L4 time plankton series in the Western English Channel is a textbook example of a shallow, stratifying shelf sea system. Over its 30 yr of weekly sampling, this site has provided a diverse and contrasting suite of numerical and conceptual models of plankton bloom formation, phenology, and seasonal succession. The most recent of these papers, Kenitz et al. (2017) has initiated this comment, partly because we feel that it has presented a slightly misleading picture of the plankton composition at this site, and of a robust, recurring seasonal succession. We address this by illustrating the extent of inter‐annual variability in phenology that occurs at the site, and which needs to be captured better within models. However our main aim is to foster a much better integration of the variety of top‐down and bottom‐up processes that have all been suggested to be key in driving seasonal succession. Some of these, particularly the multiple grazing and growth controls contributing to the so‐called “loophole hypothesis” may be complementary, but others, such as the role of copepod feeding traits in driving species succession (Kenitz et al. 2017) offer testable competing hypotheses. The basic assumptions and outputs of all these models need to be validated more critically, both against time series data and process studies that include the finding of unselective feeding. We suggest that the variability in plankton phenology (and not just mean timing and amplitude) could be used to diagnose the performance of alternative models of plankton succession.

What is the impact of systematically missing exposure data on air pollution health effect estimates? - Evangelia Samoli; Roger D. Peng; Tim Ramsay; Giota Touloumi; Francesca Dominici; Richard W. Atkinson; Antonella Zanobetti; Alain Le Tertre; H. Ross Anderson; Joel Schwartz; Aaron Cohen; Daniel Krewski; et al. (Air Quality, Atmosphere & Health, 2014)

Acute effects of ambient ozone on mortality in Europe and North America: results from the APHENA study - Roger D. Peng; Evangelia Samoli; Luu Pham; Francesca Dominici; Giota Touloumi; Tim Ramsay; Richard T. Burnett; Daniel Krewski; Alain Le Tertre; Aaron Cohen; Richard W. Atkinson; H. Ross Anderson; et al. (Air Quality, Atmosphere & Health, 2013)

Tracer tests and the structure of permeability in the Corallian limestone aquifer of northern England, UK - Aidan Foley; Gerd Cachandt; Janine Franklin; Fergus Willmore; Tim Atkinson (Hydrogeology Journal, 2012)

Constraining the uncertainty in fracture geometry using tracer tests - Peter B. Johnston; Tim Atkinson; John Barker; Noelle Odling (Hydrogeology Journal, 2009)

Book Review: Stable Isotope Geochemistry, by J. Hoefs, 2004, 340 pp. Springer, Berlin, 5th edition. Hardback price: 59.95, £46.00. ISBN 3-540-40227-6761989. - Tim Atkinson (Journal of Paleolimnology, 2005)

Use of Synchrotron Tomographic Techniques in the Assessment of Diffusion Parameters for Solute Transport in Groundwater Flow - Mark Betson; John Barker; Paul Barnes; Tim Atkinson (Transport in Porous Media, 2005)

Reliability of maximal muscle force and voluntary activation as markers of exercise-induced muscle damage - James Peter Morton; Greg Atkinson; Donald PM MacLaren; Nigel Tim Cable; Gareth Gilbert; Caroline Broome; Anne McArdle; Barry Drust (European Journal of Applied Physiology, 2005)

Porosity Imaging in Porous Media Using Synchrotron Tomographic Techniques - Mark Betson; John Barker; Paul Barnes; Tim Atkinson; Andrew Jupe (Transport in Porous Media, 2004)